Phenotypes and Baseline Risk Factors of Acute Kidney Injury in Children After Allogeneic Hematopoietic Stem Cell Transplantation - Daraskevicius, Justinas; Azukaitis, Karolis; Dziugeviciute-Tupko, Justina; Peciulyte, Milda; Planciunaite, Ruta; Vaitkeviciene, Goda; Rascon, Jelena; Jankauskiene, Augustina (Frontiers in Pediatrics, 2020)
Acute kidney injury (AKI) is a frequent and widely recognized complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Despite relatively high prevalence, AKI after allo-HSCT and its risk factors in children remain obscure. The aim of this study was to describe the prevalence and course of AKI during the first 100 days after allo-HSCT in children and to investigate its associations with baseline characteristics. Retrospective single-center chart review of all patients under 18 who underwent allo-HSCT during 2011-2017 was performed. AKI was defined using the pediatric RIFLE criteria and only the patients with pRIFLE stage I or higher were considered for the analysis. Recurrent AKI and acute kidney disease (AKD) were defined according to the Acute Disease Quality Initiative consensus. Demographic, clinical and procedure-related characteristics were recorded at day of HSCT. Fifty-one patients (68.6% boys) with a median age of nine years (range: 0.25-17) were included. During a median follow-up of 82 (IQR, 60-98) days, 27 (52.9%) patients experienced a total of 39 AKI episodes, translating into one AKI episode per 100 patient days. Multiple AKIs occurred in 11 (21.6%) patients and 18 (35.3%) progressed to AKD. Four patients died, all with ongoing or previous AKI. Patients with AKD were on average older (10 vs 6 years; p=.03) and had higher baseline body mass index (BMI) (standard deviation score (SDS) 0.83 vs 0.04, p=.05) whereas patients with recurrent AKI had higher baseline estimated glomerular filtration rate (eGFR) (244.1 vs 193.9 ml/min/1.73 m2, p=.02). In the adjusted Cox models (HR; 95% CI) older age (1.10; 1.01 to 1.20) was associated with higher risk of overall AKI, higher eGFR (1.02; 1.01-1.04) with higher risk of recurrent AKI, while older age (1.17; 1.04-1.31), higher eGFR (HR 1.01; 1.0-1.02) and higher BMI SDS (1.66; 1.01-2.72) were associated with higher risk of AKD. AKI is a frequent early complication of allo-HSCT in children and approximately one fifth experience AKI recurrence and one third develop AKD. Older age, higher BMI and higher eGFR at the day of transplant may have an effect on the risk of AKI development and its course.